Sociocultural Studies and Implications for Science Education
IX, 330 p. 110 illus., 12 illus. in color.
Keywords: The chapters included in this book address two major questions: what are some of the methodological and theoretical issues in sociocultural research in urban education and science education and what sort of questions do technological and virtual contexts raise for these types of research perspectives. The chapters build off Ken Tobin's personal history of sociocultural research in science education and as they do each chapter asks philosophical, sociological and/or methodological questions that inform our understanding of the challenges associated with conducting research in experiential and virtual contexts.